CORRELATION BETWEEN THREE COLUMN CONCEPT CLASSIFICATION AND INTERNAL FIXATION PROCEDURE OF TIBIAL PLATEAU PATIENTS AT DR. SOETOMO HOSPITAL - Utomo, Dwikora Novembri; Subiantoro, Januar Ari (JOINTS (Journal Orthopaedi and Traumatology Surabaya), 2018)
Background: Tibial Plateau Fracture is one of the most common case seen in orthopaedics and the most classification system used is Schaetzker Classification. This classification is using X ray photograph to classify the fracture and it has limitation to describing a posterior column in tibial plateau fracture since X-ray is a 2D projection. Nowadays surgeon over the world start to using Three Column concept classification because it has a better image of 3D visualization of tibial plateau.Â Purpose: To know which one classification is more accurate in describing tibial plateau fracture in Dr. Soetomo Hospital period January 2015 until September 2017.Methods: This study is retrospective study, we collected data of patients with Tibial Plateau fracture that has been operated in Dr. Soetomo hospital from January 2015 â€“ September 2017.Results: From the study found 24 patients that match with inclusion criteria. All patients are classified with Schaetzker and Three Column Classification. The most type of fracture based on Schaetzker Classification is Type 2 (7 patients) and based on Three Column Classification is type Three Column (11 patients) and the most action in Three Column type is Internal Fixation with double plate insertion (55 %).Conclusion: Three Column Classification is more accurate to describe type fracture in posterior part than Schaetzker. Three Column Classification is recommended to make easier decision for Tibial Plateau fracture treatment and prevent any loss of correction.